Hematoma of the parotid cavity revealing Eagles syndrome: a case report - Faty, Aliou; Balde, Djibril; Zounon, Alexis Arnaud Wilfrid Comlan Do Santos; Loum, Birame; Tall, Hady; Diallo, Bay Karim (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Eagle’s syndrome is characterized by elongation of the styloid process or calcification of the stylohyoid ligament, which irritates and disturbs adjacent anatomical structures. Its symptomatology is polymorphic. However, neurovascular manifestations may exceptionally be noted. We report a case of incidental discovery during an exploration for spontaneous retro-mandibular hematoma. The patient was 70 years old, Parkinsonian, with a history of untreated and chronic right retro-mandibular pain. He was admitted to the emergency room for a spontaneous retro-mandibular hematoma. A cervical CT confirmed the hematoma and revealed bilateral styloid process hypertrophy measuring 4.7 cm on the right and 4.3 cm on the left. Eagle’s syndrome is a rare disease with many clinical manifestations ranging from discomfort to severe complications. In this case, it was a spontaneous hematoma whose probable cause could be related to the long styloid process. It is important to remain attentive in cases of chronic neck pain. Any diagnostic doubt should be resolved by CT measurement of the styloid process.